THE EFFECT OF HAIR TONIC FROM SECRETOME MESENCHYMAL STEM CELL ON HAIR GROWTH IN HAIR LOSS CASES - MARLINA; NOVITA, NELLA; ANDAYANI, REGINA (International Journal of Applied Pharmaceutics, 2026)
Objective: This study aims to determine the optimum concentration of secretome from mesenchymal stem cells (MSC) in a hair tonic formulation and evaluate its effect on hair growth in individuals experiencing alopecia. Methods: Tweenty volunteers were divided into five groups to test various hair tonic formulations over eight weeks. Each group received a different concentration of MSC secretome (5%, 7%, 10%) while negative controls consisted of fetal bovine serum and hair tonic base without MSC. Hair density was measured before and after the treatment period to assess the impact of each formulation. Results: The formulations containing adipose tissue mesenchymal stem cell (ATMSCs) secretome significantly influenced hair growth, with the 10% secretome concentration showing the most substantial increase in hair density among the volunteers. Analysis revealed that the 10% formulation had higher levels of vascular endhotelial growth factor (VEGF) compared to the 5% and 7% formulations, indicating a correlation between VEGF concentration and the stimulation of hair follicle activity. Conclusion: The MSC hair tonic formula enhanced the hair density of participants after eight weeks, indicating its potential as a treatment to stimulate hair growth in those with alopecia. The study concludes that a higher concentration of MSC secretome specifically 10%, may yield optimal results in promoting hair regeneration.